Interdisciplinaridade: contributos da inteligência artificial para a Ciência da Informação - Costa, Tâmela; Coneglian, Caio Saraiva; Benin, Keli Rodrigues do Amaral; Oliveira, Henry Poncio Cruz de; Vidotti, Silvana Aparecida Borsetti Gregório (Informação em Pauta, 2025)
Objective: to verify the possible contributions of Artificial Intelligence in the application areas of Information Science. Methods: This is an integrative literature review investigated from the following information sources: Reference Database of Journal Articles in Information Science, Scopus, and Library and Information Science Abstracts. The search strategy was based on the terms "artificial intelligence" and "information science". Results: Sixty-four articles found on the topic of the contributions of artificial intelligence to information science were grouped into the following categories: Interdisciplinarity; Organization and Management of Information; Applicability; and Knowledge Management. Conclusions: The study confirmed that Artificial Intelligence is interdisciplinary, allowing connections with other areas of knowledge, and that there is evidence of contribution in the applied area of Information Science.